Implementation of a test rig to characterize the process suitability of filaments for 3D printing (Transactions on Additive Manufacturing Meets Medicine, 2019)
While the use of new types of filaments in 3D printing expands the range of applications, an answer to the question whether the new materials can be processed well requires time-intensive testing on actual printers. In order to be able to check potentially processible materials before starting printing, a prototype test bench was developed that replicates the process of a conventional 3D printer. With this setup, filaments can be extruded at specific temperatures and speeds. Furthermore, the feed force is measured while speed and temperature are iterated. The measurements obtained in this way can be visualized and exported.